Characterization of lysine crotonylation-related lncRNAs for prognostic assessment and immune response in glioma - Song, Miaomiao; Xu, Juan; Gui, Zhonghao; Wu, Yun; Wang, Feifei; Sheng, Hongmei; Huang, Xueyong; Qian, Junyu; Qin, Haotian; Wang, Ying (Frontiers in Pharmacology, 2025)
BackgroundGlioma is a highly aggressive brain tumor with limited therapeutic options and poor prognosis. While immune checkpoint inhibitors and molecular therapies have emerged, effective biomarkers for patient stratification remain scarce. Long non-coding RNAs (lncRNAs) associated with lysine crotonylation (LCRlncRNAs) have been implicated in cancer progression, but their role in glioma remains largely unexplored.MethodsTranscriptomic and clinical data from The Cancer Genome Atlas (TCGA) glioma cohort were analyzed to identify prognostic LCRlncRNAs. A multigene risk score model was constructed using univariate Cox, LASSO, and multivariate Cox regression analyses. Functional enrichment analyses (GO, KEGG, GSEA) and immune landscape profiling (CIBERSORT, ssGSEA, ESTIMATE) were performed to explore potential mechanisms. Associations with immune checkpoint expression, tumor mutational burden (TMB), and microsatellite instability (MSI) were also assessed. In addition, RT-qPCR, EdU, Transwell, and xenograft experiments, as well as qPCR, Western blot, serum ELISA, and immunohistochemistry (IHC) analyses, were conducted to validate the functional and mechanistic roles of the representative LCRlncRNA POLR2J4.ResultsSix LCRlncRNAs were identified as independent prognostic factors, and the risk score model stratified patients into high- and low-risk groups with distinct survival outcomes. The high-risk group exhibited enriched immunosuppressive features, including increased regulatory T cells, M2 macrophages, and elevated expression of immune checkpoints (e.g., PD-L1, CTLA4). TIDE analysis indicated poor immunotherapy response in high-risk patients. Drug sensitivity analysis revealed that high-risk patients were more sensitive to DNA-damaging agents such as cisplatin. Functional assays confirmed that POLR2J4 promotes glioma proliferation, migration, and cisplatin resistance. Mechanistically, POLR2J4 knockdown reduced the expression of drug resistance genes (ABCB1, ABCC1, BCL2), decreased serum levels of IL-6 and TGF-β1, and downregulated TGF-β1 and PD-L1 in tumor tissues, highlighting its role in establishing an immunosuppressive, drug-resistant microenvironment.ConclusionOur study demonstrates that LCRlncRNAs are closely linked to glioma prognosis, immune microenvironment remodeling, and therapeutic response. The LCRlncRNA-based risk model provides a promising tool for prognostic evaluation and personalized therapy design in glioma.